AN ANALYSIS OF GENDER INTEGRITY IN CORRELATION WITH ADVANCEMENT OF WOMEN’S RIGHTS IN INDIA - Dr. Bharati S. Dodamani (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Gender justice implies the absence of any discrimination on the basis of sex. The term gender generally means cultural or attitudinal qualities that are characteristics of a particular sex. The term ‘sex’ is commonly used to denote one’s status as a man or woman based upon biological factors. The term gender generally means cultural or attitudinal qualities that are characteristics of a particular sex. The concept of ‘Gender Justice’ is a recent discovery of law. From time immemorial society has been male dominated, with women relegated to the background and their rights trampled upon. It is only recently that women began to assert their rights and the law recognized that men and women have equal rights. The concept of ‘Gender Justice’ sprouted thus. Conventionally, gender justice refers to the equal, equitable and even handed treatment of women in social, political and economic domain. Although, social behaviour and outlook have to undergo a change to bring about gender justice, there is lurking possibility that law and the courts can abet stereotyping of women and thwarting their quest for justice. The Constitution of India not only ensures equality to women but also empowers the State to adopt measures of positive discrimination in favour of women for neutralizing the cumulative socio economic, education and political disadvantages faced by them. Fundamental Rights, among others, guarantees equality before the law and equal protection of law, prohibits discrimination against any citizen on grounds of religion, race, caste, sex or place of birth, and guarantee equality of opportunity to all citizens in matters relating to employment.